Radiation Dose for 345 CT-Guided Interlaminar Lumbar Epidural Steroid Injections - Chang, A.L. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: CT guidance is increasingly being used to localize the epidural space during epidural steroid injections. A common concern is that CT may be associated with significantly higher radiation doses compared with conventional fluoroscopy. The goal of this retrospective study was to determine the average dose-length product and effective dose delivered while interlaminar epidural steroid injections are performed and allow comparison with other modalities. MATERIALS AND METHODS: A total of 281 patients who had undergone 345 consecutive CT-guided epidural steroid injections of the lumbar spine were evaluated for radiation exposure. The dose-length product for each scan was derived from the CT dose index volume and scan length. Effective dose was then calculated from the dose-length product and a κ coefficient of 0.015. Procedure time was calculated from the PACS time stamp on the scout image to the last CT image of the last image series. RESULTS: The average dose-length product across all procedures was 89.6 ± 3.33 mGy·cm, which represents an effective dose of 1.34 ± 0.05 mSv. No complications from the procedure were observed, and average procedure time was 8 minutes. CONCLUSIONS: The use of a stationary table and an intermittent scanning technique allow for short procedures and doses that are significantly lower than those of conventional diagnostic CT scans. Furthermore, because CT dose index overestimates radiation dose in stationary table procedures, the actual radiation dose may be even lower than stated here.